KONSEP KEDERMAWANAN (JUD) DAN KEADILAN (‘ADL) ILAHI DALAM FILSAFAT AL-FARABI - Hatice Toksoz (VIRTUOUS JOURNAL, 2024)
The foundation of al-Fârâbî’s metaphysical system is comprised of two concepts; divine providence (inayah/alcûd) and justice (adl). The concepts of providence and justice are closely related to metaphysics, ethics, and political philosophy in the thought of al-Fârâbî. These two concepts are also attributes of Allah. al-Fârâbî explains his ideas on the perfection of the universe by expanding on these two concepts. According to the philosopher, the universe has a perfect order which is a result of God’s attributes of al-cûd and justice. He also considers the universe like a human being and compares it to a human organism.